MENINGKATAN KEMAMPUAN MEMBACA PERMULAAN ANAK USIA 5-6 TAHUN DENGAN METODE FONIK DI TK ISLAM DARUNNAJAH ULUJAMI - Pipit Nuri Mulyaningtias; Kusyanti Febriana (Awladuna: Jurnal Pendidikan Islam Anak Usia Dini, 2024)
Enhancing Early Reading Skills in Children Aged 5-6 Years at TK Islam Darunnajah Using the Phonics Method. Thesis: Early Childhood Islamic Education Program (PIAUD), Faculty of Islamic Studies, Universitas Darunnajah Jakarta 2024, pages, images, tables, graphs, appendices.This research is motivated by the importance of early reading skills for children from an early age. These early reading skills will later serve as a gateway for children to enter higher levels of education. However, in reality, many children still have low early reading abilities. Many children are not yet familiar with letters and letter sounds, and they struggle to read syllables. The purpose of this research is to improve early reading skills in children aged 5-6 years using the phonics method at TK Islam Darunnajah Ulujami. This research employs a classroom action research method, which includes planning, action, observation, and reflection. From the results of the pre-cycle observation, it was found that the average early reading ability of the children was 42.2%. After implementing the first cycle, it increased to 63.4%, and after the second cycle, it further increased to 81.4%. This indicates that the early reading skills of children aged 5-6 years at TK Islam Darunnajah can be improved using the phonics method.